(untitled) (Interdisciplinary Studies Journal, 2024)
The present article characterizes provisional test for cocaine verification that standardized in Law nº 11.343, of August 23, 2006, whose positive result is enough for purpose of drawing up arrest in flagrante delicto act. Thus, people involved at facts may be wrongly arrested due technical limitations applied by chemical methods selected by forensic experts at time of aforementioned examination and, in addition, misconduct during the analyzes can cause harm to environment considering the toxic potential of reagents normally used. Given this situation, this work, based on a qualitative research, sought to build an analytical protocol for Núcleo de Perícias Criminalísticas de Presidente Prudente. The research methodology for selecting methods was based on establishing following criteria: low cost, photographic record, examination time, effective sensitivity and selectivity, and environmental care; from literature review and also by experimental tests carried out in forensic chemistry laboratory of the aforementioned nucleus. In view results obtained, the proposed analytical protocol consists Thin Layer Chromatography (TLC) with Cyclohexane(75):Toluene(15):Diethylamine(10) solvent system and Scott’s colorimetric test.